Imagining terminality: anticipations of suicide with assistance in Switzerland - Berthod, Marc-Antoine; Stavrianakis, Anthony; Pillonel, Alexandre; Dransart, Dolores Angela Castelli (Revista M. Estudos sobre a morte, os mortos e o morrer, 2019)
This article explores how people who solicit assistance in dying imagine and anticipate their own terminality. Its objective consists in describing and interpreting the fact that these individuals go beyond their medical condition when commenting on such a request and on their engagement in this process. Based on an ongoing ethnographic inquiry funded by the Swiss Science Foundation and carried out in Switzerland, where assistance with suicide is permitted within a unique legal framework, the article shows the importance of taking into consideration the role that affective and imaginative internalized contents – imagination, broadly conceived – play in the realization of assisted suicide. These contents are key to appreciating a decision to request to die with assistance as well as its justifications.